IMF and the challenges of globalization : three address - Camdessus, Michel ([IMF] [Washington]US, 1995)
Indicates possible ways in which the IMF can increase its effectiveness in helping to minimize the risks to the world economic outlook - risks magnified by financial globalization. Highlights the lessons learnt from Mexico's financial crisis and the conduct of economic policy, the role of the IMF and international cooperation. Looks at Africa's economic challenges.